Standard approach to gastrointestinal stromal tumors: differences between China and Europe - Tu, Lin; Hohenberger, Peter; Allgayer, Heike; Cao, Hui (Visceral medicine, 2018)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract. With the considerable research and application of molecular-targeted therapy for GISTs in the last two decades, GISTs have become a model of multidisciplinary oncological treatment. Although Western clinical guidelines are available for GISTs, such as those by the European Society of Medical Oncology (ESMO), the clinical situations in China are different from those in European countries. There are distinct differences between the clinical practice, diagnostic methods, surgical approach, and availability of new targeted agents in China and those in Europe. This review summarizes the Chinese GIST consensus guidelines compared to the European ones, which may provide an optimal approach to the diagnosis and management of GIST patients.
Gesehen am 14.06.2019